Improvement of Science Learning Outcomes Through the Discovery Learning Model Students of Class V SDN 02 Sarwodadi - Amelia, Ratih (Universitas Sebelas Maret, 2020)
The purpose of this study is to improve the science learning outcomes competency in analyzing the relationship between ecosystem components with the Discovery Learning model. The subjects in this study were students of class V SDN 02 Sarwodadi, consisting of 14 boys and 6 girls. Classroom Action Research Methods implemented in 3 cycles. The research design starts from the planning stage, action implementation, observation, and reflection. The learning outcomes of students with the application of the Discovery Learning model have increased in each cycle. In cycle I (75%), cycle II (87.50%) and cycle III (100%). Completeness of learning in cycle I (70%), cycle II (90% and cycle III (100%) while the class average in cycle I (76.50), cycle II (83.00), and cycle III (85, 50) The conclusion that can be drawn is that learning with the use of the Discovery Learning model can improve science learning outcomes competence in analyzing the relationship between ecosystem components in class V SDN 02 Sarwodadi students.